A reader's guide to William Faulkner : the novels - Volpe, Edmond Loris (Syracuse, N.Y. : Syracuse University Press, 2003)
Presents a comprehensive guide to the works of William Faulkner and provides a detailed analysis of several of his novels along with a profile of his life and career.
Originally published: New York : Farrar, Strauss, 1964.
Includes bibliographical references (p. [413]-422) and index.
Adult
Keywords: Faulkner, William, -- 1897-1962 -- Criticism -- Handbooks, manuals, etc; Faulkner, William, -- 1897-1962 -- Examinations -- Study guides